Integral characteristics of the students of the Bachelor's Degree in Psychology of the Faculty of Humanities, Social Sciences and Guarani Culture - National University of Itapúa, year 2016 (UNIHumanitas, 2019)
The intelligence, behavior and personality of the students of the Bachelor's degree in Psychology constitute the central axes in their formation within the professional field. The main objective of this work was focused on the description of the integral characteristics, involving the areas of intelligence levels, personality and qualification in terms of behavior of the students of the Psychology career of the Faculty of Humanities, Social Sciences and Guarani Culture. The approach was quantitative, with a cross-sectional, descriptive design. It was carried out with a sample of 36 students during the 2016 academic year. Data were collected using instruments such as the Raven's Test (general scale), the MMPI-2 and a Survey for Teachers in order to evaluate areas such as: personality, behavior and intelligence level of each of the students. In the level of intelligence, the students are located between the Above Average and Below Average ranges in terms of IQ. In relation to behavior, most of them are in the range that corresponds to excellent behavioral performance. And as for personality characteristics, most of the students who made up the study sample are outside the normal ranges, being located in risk zones according to the basic scales of the MMPI-2.
Keywords: psychology; cognition; personality; intelligence